Lexical-Semantic Analysis of the Concepts of «Bankruptcy Procedure» and «Bankruptcy Process» - Битківська, А. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Currently in the unstable political and economic situation in the country and increased risk of unprofitableness of national enterprises, topics of bankruptcy is quite relevant. The Bankruptcy Law characterize by a certain imperfection, namely the defining the essence of the fundamental categories. Thus, despite the intensive use of the concepts of «bankruptcy procedure» and «bankruptcy process» their definition is missing as in the legislation as in the scientific literature. In this regard, the article examines the essence of the categorical apparatus of the phenomenon of bankruptcy. Done lexical-semantic analysis of the concepts of «bankruptcy procedure» and «bankruptcy process» As a result formulated the definition of «bankruptcy procedure» and found that the bankruptcy procedure proceedings in its content is only the liquidation procedure and the procedure of the settlement agreement, if signed after the recognition of the debtor bankrupt. Procedures disposition of property, sanitation readjustment (judicial and extrajudicial), the settlement agreement in the case its conclusion before declaring the debtor bankrupt, offered to determine as recovery procedures of solvency. It is established that the procedure is part of a process, bringing the essence and is defined content of concepts the «bankruptcy process» and «process of restoring solvency». Identifies the components and limits of these processes in the structure of the crisis period activity of the enterprise related with the loss of solvency and the threat of bankruptcy.